The Effect of Resource-Based Learning Model on Problem Solving Ability of Students at SMA Adabiyah Palembang - Lolita Resiana Puteri; Jamiatul Khairunnisa Putri; M. M. Jhoni; Suhadi Suhadi; Faizatul Mabruroh; Andi Putra Sairi; Herma Widya; Nurhamidah Nurhamidah (Jurnal Pembelajaran Fisika, 2022)
The purpose of this study was to determine the significant effect of the Resource-Based Learning model on students' problem-solving abilities. This research uses experimental quantitative research methods. The technique used is using a saturated sampling technique which can be called a census sample selection where all members of the population are sampled. The data analysis technique of this research is to compare the test results of the experimental class and the control class by using the pre-test and post-test normality test, homogeneity test, and hypothesis testing. The results showed that there was a significant effect on the experimental class that had been treated with the Resource-Based Learning (RBL) model on the problem-solving ability of light waves at SMA Adabiyah Palembang, this was evidenced by the results of the problem-solving abilities of the experimental class and the control sample class. From these results, the average problem-solving ability of the experimental class is greater than that of the control class. Then from the analysis obtained using IBM SPSS 15.0 with a t-test value of 0.000 <0.05, it can be concluded that there is an influence of the Resource-Based Learning (RBL) learning model on the ability to solve light wave material physics problems at SMA Adabiyah Palembang.Keywords: Learning model, Resource-based learning, Problem solving abilityDOI: http://dx.doi.org/10.23960/jpf.v10.n2.202204